A comparative study on wave-deck interactions of T-type and box girder decks under regular waves. (1st July 2021) - Chen, Xuebin; Xu, Wei; Lin, Chong; Sun, Hongwei; Zeng, Xiaofang; Liu, Qiaoyu; Chen, Shiguang
Abstract: Extreme wave forces have damaged massive coastal bridges in the past decades. To the best knowledge of the authors, a direct comparison of dynamic wave-deck interactions between T-type and Box girder decks under the same wave conditions has not been studied. This paper establishes a numerical model solving the Navier-Stokes equations for viscous and incompressible free surface flows, which is verified by existing experimental data. A total of 54 numerical experiments based on this model are then carried out to investigate the dynamic responses of two bridge decks under various wave conditions, and the influences of hydrodynamic parameters on the wave-deck interaction are studied. Two peak values are found in the curve of lateral displacement versus dimensionless submersion depth for the T-type girder deck, while one peak value is found in the curve for the Box girder deck. The relations between lateral displacement and period for two decks are both uncertain, which highly depends on the submersion depth and girder type. The lateral displacement is positively correlated with the wave height for two bridge decks, which is only valid when the horizontal wave force in the specified wave height is large enough to overcome the frictional force. This study provides researchers an insight into the difference of instantaneous lateral displacement between two most commonly used cross-section shapes of bridge deck, and helps to further understand the fragility of T-type and Box girder decks under extreme waves. Highlights: A numerical model for studying the wave-deck interactions of T-type and Box Girder Decks under regular wave is proposed. Numerous simulations are carried out to investigate the dynamic responses of two bridge decks under various wave conditions. The parameter influences on lateral deck displacements are studied, and the failure mechanisms for two decks are discussed.